Functional programming in Scala - Pilquist, Michael; Bjarnason, Rúnar; Chiusano, Paul (Manning Publications Co., 2023)
Functional Programming in Scala has helped over 30,000 developers discover the power of functional programming. You’ll soon see why reviewers have called it “mindblowing”! The book smooths the complexity curve of functional programming, making it simple to understand the basics and intuitive to progress to more advanced topics. Concrete examples and exercises show you FP in the real world and reveal how it can improve your everyday coding practices. This second edition comes packed with the latest standards of FP, as well as full code updates to Scala 3, and its new language features.